Identification of compound heterozygous variants in OPTN in an ALS-FTD patient from the CReATe consortium: a case report. Issue 5 (3rd July 2018) - Pottier, Cyril; Rampersaud, Evadnie; Baker, Matt; Wu, Gang; Wuu, Joanne; McCauley, Jacob L.; Zuchner, Stephan; Schule, Rebecca; Bermudez, Christin; Hussain, Sumaira; Cooley, Anne; Wallace, Marielle; et al.
Abstract: Homozygous loss-of-function mutations in optineurin ( OPTN ) are a rare cause of amyotrophic lateral sclerosis (ALS), whereas heterozygous loss-of-function mutations have been suggested to increase ALS disease risk. We report a patient with ALS and frontotemporal dementia (FTD) from the Clinical Research in ALS and Related Disorders for Therapeutic Development (CReATe) Consortium carrying compound heterozygous loss-of-function variants in OPTN . Quantitative real-time mRNA expression analyses revealed a 75–80% reduction in OPTN expression in blood in the OPTN carrier as compared to controls, suggesting at least partial nonsense-mediated decay of the mutant transcripts. This case report illustrates the diverse inheritance patterns and variable clinical presentations associated with OPTN mutations, and underscores the importance of complete OPTN gene screening in patients with ALS and related disorders, especially in the context of clinical genetic testing.